NATO’s Social Media Strategic Communication in the Making (Altre Modernità, 2018)
The tenet of this investigation, stemming from Conoscenti (2016 and 2017), is that since 2014 the NATO military have been unable to introduce specific correctives to their social media strategy, particularly on Facebook, thus endangering their role and strategic capabilities. This paper builds on the chance that the author had to attend and lead, as a subject-matter expert, the NATO working groups that are active in this specific communicative environment. This also offered him the opportunity to be a participant observer and to access specific documents of the discourse community under scrutiny. After clarifying the elements that frame the military operations in this field, the current NATO communication on Facebook will be analysed in contrast to its communication in 2014. The paper also aims to document the effort of younger military generations to adapt to this new scenario. To account for this, an analysis of military discourse methodology is used. To achieve this goal a multimodal analysis approach (Conoscenti, 2017; Norris, 2011; Kress, 2010) is blended with netnography (Kozinet, Dolbec and Earley, 2014). Since the NATO Facebook page is a specific case of Computer-Mediated Communication to be analysed with a Discourse Analysis perspective that incorporates content analysis, this can be achieved through an extended paradigm of WebCA (Herring, 2010).
Keywords: English Linguistics; NATO; CMC; WebCA; Analysis of Military Discourse; Social Media